2020
DOI: 10.1111/apv.12260
|View full text |Cite
|
Sign up to set email alerts
|

Livelihoods, leadership, linkages and locality: The Simbo for Change project

Abstract: This paper analyses the ‘Simbo for Change’ project in the Western Province of Solomon Islands, a collaboration between Simbo leaders and a Samoan non‐governmental organisation (NGO), with funding provided by the Australian aid programme. We explore the role of local leadership in catalysing an island‐wide community development project that has generated new livelihoods opportunities and led to greater community cohesion and more proactive governance. By mobilising around a ‘collective subject’ (Simbo as an isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Whilst this approach aimed to circumvent some of the challenges found in the IACCA-EUM programme, as Jabeen (2018) notes, "bypassing the elite and giving key positions to the poor might create friction (even if transitory) in a community" (pp.264), and damage social cohesion. Social cohesion and livelihood opportunities are closely linked (Suti et al, 2021;Jensen, 2019) and have been shown to be critical for building livelihood resilience (Mitra et al, 2017;Townshend et al, 2015). Some argue that institutional arrangements cannot be transferred, such as with technologies, but that they should emerge from the context in which they operate (Biggs, 2007).…”
Section: Differentiated Experiences Of Innovation Processesmentioning
confidence: 99%
“…Whilst this approach aimed to circumvent some of the challenges found in the IACCA-EUM programme, as Jabeen (2018) notes, "bypassing the elite and giving key positions to the poor might create friction (even if transitory) in a community" (pp.264), and damage social cohesion. Social cohesion and livelihood opportunities are closely linked (Suti et al, 2021;Jensen, 2019) and have been shown to be critical for building livelihood resilience (Mitra et al, 2017;Townshend et al, 2015). Some argue that institutional arrangements cannot be transferred, such as with technologies, but that they should emerge from the context in which they operate (Biggs, 2007).…”
Section: Differentiated Experiences Of Innovation Processesmentioning
confidence: 99%
“…The Kulu Language Institute resonates with other grassroots social movements that have re-valued local ways of life in periods of rapid social, economic and political change. One such movement has been thriving in Ranongga's nearest neighbour-the 'Simbo for Change' movement focuses on local livelihoods and has inspired a 'revitalised ethic of care for the island' (Suti, Hoatson, Tafunai & Cox, 2020). Many such movements have centred on what is known in neo-Melanesian languages as kastom.…”
Section: Discussionmentioning
confidence: 99%
“…Community‐led efforts and traditional knowledge systems that prioritise active local communities in leading adaptation strategies have emerged as central strategies in responding to these significant challenges (Salick and Ross, 2009; Mcleod et al ., 2018; Roche et al ., 2020). Such approaches work because they incorporate collective, community‐based responses to environmental, economic and social challenges which better reflect Melanesian culture (Suti et al ., 2021). Throughout the Pacific Islands, indigenous peoples have extensive knowledge of the land and sea environments and long records of successful management of ecological environments (Brodie et al ., 2013; Lebel, 2013; Fache et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%